The Perennial Thirty Years' War - Ulrika Carlsson (London School of Economics and Political Science (LSE), European Institute, 2018)
I argue that the conflict that arose in Europe as a result of the Reformation and culminated in the Thirty Years' War persists to this day, as the two spirits corresponding respectively to Protestantism and Catholicism continue to divide us. Analyzing phenomena such as the Pepsi Challenge and the French resistance to headscarves, I argue that this culture war is a war between an aesthetic and a moralistic worldview. I defend one of these as life-affirming and condemn the other as life-denying.
Keywords: 330